(3x-2y)(2x-2y+3)-10=0

Simple and best practice solution for (3x-2y)(2x-2y+3)-10=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-2y)(2x-2y+3)-10=0 equation:


Simplifying
(3x + -2y)(2x + -2y + 3) + -10 = 0

Reorder the terms:
(3x + -2y)(3 + 2x + -2y) + -10 = 0

Multiply (3x + -2y) * (3 + 2x + -2y)
(3x * (3 + 2x + -2y) + -2y * (3 + 2x + -2y)) + -10 = 0
((3 * 3x + 2x * 3x + -2y * 3x) + -2y * (3 + 2x + -2y)) + -10 = 0

Reorder the terms:
((9x + -6xy + 6x2) + -2y * (3 + 2x + -2y)) + -10 = 0
((9x + -6xy + 6x2) + -2y * (3 + 2x + -2y)) + -10 = 0
(9x + -6xy + 6x2 + (3 * -2y + 2x * -2y + -2y * -2y)) + -10 = 0

Reorder the terms:
(9x + -6xy + 6x2 + (-4xy + -6y + 4y2)) + -10 = 0
(9x + -6xy + 6x2 + (-4xy + -6y + 4y2)) + -10 = 0

Reorder the terms:
(9x + -6xy + -4xy + 6x2 + -6y + 4y2) + -10 = 0

Combine like terms: -6xy + -4xy = -10xy
(9x + -10xy + 6x2 + -6y + 4y2) + -10 = 0

Reorder the terms:
-10 + 9x + -10xy + 6x2 + -6y + 4y2 = 0

Solving
-10 + 9x + -10xy + 6x2 + -6y + 4y2 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| 11.95+1.71=0 | | 13+p=-3+4(4+6p) | | (6m-3)+m-4=0 | | 55n+210= | | 11.95+1.71= | | 0.7x+0.8=5.7 | | 6/1/5=1/4/m | | f(x)=0.5-2x+5 | | 8x+1=2x+40 | | x+(x*.15)=30 | | x+(x*.15)=25 | | 6(1+2x)=5(3-x)+25 | | 6x^2-18x-12=0 | | 7x+12=3(2x+9) | | x/4y=19 | | 2x^2+mx+9=0 | | 6x+8x=12 | | t=144.67+0.39m | | [x-4]=6x+16 | | (1/7÷4/5)×7/9 | | g-8=-2 | | 2e^3x-1=9 | | 8/7m-36/7=12 | | 8/7m-36=12 | | X^2+4x-360=0 | | 23/x=23/4/5 | | 15y-10y=15 | | (x+5)+(2x+25)=90 | | ((z-4)/6)-2=(z/2) | | 5/3-3/4 | | (-9x)-22=(-3x)-4 | | 1/4(8x-12) |

Equations solver categories